Prognostic factors associated with mortality in patients with septic arthritis: a descriptive cohort study. (2nd January 2017) - Andreasen, RA; Andersen, NS; Just, SA; Christensen, R; Hansen, IMJ
Abstract : Objectives : To evaluate the 30-day mortality rate of septic arthritis (SA) in adults in Funen, central Denmark, and to explore whether, at the time of SA presentation, risk factors for the 30-day mortality rate could be revealed. Our secondary objective was to describe the microbiological aetiologies, systemic signs of inflammation, and co-morbidity. Method : A descriptive study identifying patients with SA from central Denmark, during the period 2006–2013, by the use of joint fluid culture data retrieved from the electronic database at the Department of Clinical Microbiology, Odense University Hospital. Patients with a positive joint fluid culture were considered eligible and their medical records were examined. Results : We identified 215 patients with SA, mean age 64.8 years. At presentation, mean C-reactive protein (CRP) was 204 mg/L, mean white blood cell count (WBC) 11.9 × 10 9 /L, and mean body temperature 37.6°C. A total of 101 patients (47%) had a prosthetic joint, 46 (21%) had an inflammatory joint disease, and 24 (11%) had diabetes mellitus (DM). Staphylococcus aureus was the most common pathogen (104 patients, 48.4%). The 30-day mortality rate was 9.3% and the significant risk factor for death was liver disease at time of presentation [odds ratio (OR) 40.40, 95% confidence interval (CI) 5.38–303]. The other factors tested such as age > 65 years, elevated temperature, rheumatoid arthritis (RA), prostheses, and diabetes mellitus (DM) did not reach statistical significance. Conclusions : In our sample of patients with SA, we found a 30-day mortality rate in almost one in 10 adults. Among possible explanations, our study indicates that liver disease is a clinically relevant risk factor.